Music & IA: Requiem or Symphony. - Olcoz Basarte, Iñigo; Eslava Arraiza, Sergio; Arbona Puértolas, Leire; Morrás Andrés, Esteban (Revista Internacional de los Estudios Vascos, 2024)
In the current era where Artificial Intelligence (AI) is leading to the automation of cognitive skills that were previously only imaginable within the capabilities of human intelligence, and where the synthetic generation of art in the field of musical composition is also reaching the general public, we wonder whether the impact of Artificial Intelligence on music will lead to a democratisation of new possibilities for artistic expression or, on the contrary, will result in a trivialization that leads to a progressively lower musical quality. To address this question, this article embarks on a journey through the historical dialectic between music and technology, seeks parallels in disciplines such as chess that have undergone similar processes, explores the inseparability between merit and artistic outcome and between musical and extra-musical factors, analyses the recent and current impact of algorithmics on avant-garde musical composition, reviews the current legal and juridical status regarding musical authorship, and ethically reflects on Artificial Intelligence through the experience of working daily with AI tools. Our conclusion is that music must prevail, because the human being must prevail.